Aggregate stability in two cropped and no-cropped Oxisols as affected by phosphate addition and mycorrhiza - Nóbrega, Júlio César Azevedo; Lima, José Maria de; Curi, Nilton; Siqueira, José Oswaldo; Motta, Paulo Emilio Ferreira da (Pesquisa Agropecuaria Brasileira, 2001)
In the tropics there is little information on the contribution of soil microorganisms on aggregate stability in the soils. Soil management, crop and fertilization can affect the fungi specie in soil, and also affect aggregate stability. This study attempted to evaluate the effect of earlier cropping, phosphate, inoculation with AMF, and brachiaria and soybean on the geometric mean diameter (GMD), particle flocculation index, root dry matter, and total hyphal length, in dystrophic Red Latosol and dystroferric Red Latosol (both Oxisols). Samples of both soils under natural condition and previously cultivated were brought to the green house and received P fertilization and inoculation. Then, they were cultivated twice with brachiaria and soybean. The results showed that the previously cultivated soils had lower total hyphal length and lower aggregate stability (lower GMD), whereas inoculation increased these parameters according to P level. Phosphate fertilization had an indirect benefit on aggregate stability by increasing total hyphal length and root dry matter.